PENCIPTAAN DESTINATION BRANDING KAWASAN WISATA B-29 KABUPATEN LUMAJANG SEBAGAI UPAYA MEMPERKENALKAN OBYEK WISATA BARU - Abdullah, Ali; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: design creation of Destination Branding tourist area B-29 is promotional efforts, provide information about natural attractions inside are cultures that can be preserved and can become one of the new tourist attractions in Indonesia The study was conducted using qualitative methods is by doing interviews, observation ,documentation, and literature to obtain data used as drafting the manufacture of Destination Branding. Concept or keyword obtained through data analysis, keyword analysis performed Based on the acquired keyword is "Panorama Suci Gunung Bromo" keyword is defined operationally and conceptually. Those keywords have 3 words that panorama, sacred, Mount Bromo. Meaning panorama according to KBBI natural landscape broad definition of operational panorama can be conceptualized as natural beauty, which is described as seeing Mount Bromo sacred significance display of the ritual performed residents in the area B-29, where the ritual process is laden with religious values that based on the sainthood. KBBI interpreted in the holy purity or cleanliness as a heart and something holy. Mount Bromo words in the keyword in getting from the uniqueness of the area B-29 where visitors can see the other side of Mount BromoÂ Keywords: Creation, Destination Branding, tourist areas B-29, Tourism Lumajang